Administrative incidence of psychosis assessed in an early intervention service in England: first epidemiological evidence from a diverse, rural and urban setting. - Cheng, F; Kirkbride, J; Lennox, B; Perez, J; Masson, K; Lawrence, K; Hill, K; Feeley, L; Painter, M; Murray, G; Gallagher, O; Bullmore, E; et al. (2011)
BACKGROUND: Early Intervention in Psychosis Services (EIS) for young people in England experiencing first-episode psychosis (FEP) were commissioned in 2002, based on an expected incidence of 15 cases per 100 000 person-years, as reported by schizophrenia epidemiology in highly urban settings. Unconfirmed reports from EIS thereafter have suggested higher than anticipated rates. The aim of this study was to compare the observed with the expected incidence and delineate the clinical epidemiology of FEP using epidemiologically complete data from the CAMEO EIS, over a 6-year period in Cambridgeshire, for a mixed rural-urban population. METHOD: A population-based study of FEP (ICD-10, F10-39) in people aged 17-35 years referred between 2002 and 2007; the denominator was estimated from mid-year census statistics. Sociodemographic variation was explored by Poisson regression. Crude and directly standardized rates (for age, sex and ethnicity) were compared with pre-EIS rates from two major epidemiological FEP studies conducted in urban English settings. RESULTS: A total of 285 cases met FEP diagnoses in CAMEO, yielding a crude incidence of 50 per 100 000 person-years [95% confidence interval (CI) 44.5-56.2]. Age- and sex-adjusted rates were raised for people from black ethnic groups compared with the white British [incidence rate ratio (IRR) 2.1, 95% CI 1.1-3.8]. Rates in our EIS were comparable with pre-EIS rates observed in more urban areas after age, sex and ethnicity standardization. CONCLUSIONS: Our findings suggest that the incidence observed in EIS is far higher than originally anticipated and is comparable to rates observed in more urban settings prior to the advent of EIS. Sociodemographic variation due to ethnicity and other factors extend beyond urban populations. Our results have implications for psychosis aetiology and service planning.